Challenges Associated with Eradicating Invasive Rodents from Islands: Lessons Learned - Gill, Chris; Wein, Laurie; Howald, Gregg; McClelland, Pete (Proceedings of the Vertebrate Pest Conference, 2014)
Removal of introduced rats from islands is a proven and powerful conservation tool that can help restore ecosystem functioning and/or processes. Haida Gwaii, British Columbia, Canada, is an isolated marine archipelago with distinct flora and fauna that have evolved during 14,000 years of isolation from the mainland. Approximately 1.5 million seabirds from 13 species nest on the islands of Haida Gwaii, including 50% of the global ancient murrelet population, a federally designated species at risk in Canada. Within Gwaii Haanas National Park Reserve and Haida Heritage Site (located at the southern end of Haida Gwaii) there are 9 designated Important Bird Areas (IBAs), established primarily to denote important seabird nesting sites. However, unintentional historical introductions of rats to islands within IBAs and throughout Haida Gwaii have led to the demise of several seabird nesting colonies. In September 2013, Parks Canada Agency, in partnership with Coastal Conservation and Island Conservation, implemented Canada’s first aerial broadcast eradication of black rats from two islands within the Ramsay Island and Northern Juan Perez Sound Islands IBA, where seabird colonies and ecosystem processes have been negatively impacted by this species. The eradication of black rats from Murchison and Faraday Islands posed several challenges including ensuring adequate bait density to maximize the probability of eradication success while minimizing risks to native species. Our planning efforts focused on addressing bait competition by non-target species, the consequence of bait interception by the forest canopy, minimizing bait entering the marine environment, mitigating potential negative impacts to non-target species, and determining the ideal timing for the eradication operation. We present here a summary of these challenges and the measures that were implemented to address them.